Trajetórias do planejamento urbano: O plano diretor da década de 1950 e o reordenamento urbano de Araraquara-SP - De Toledo, Rodrigo Alberto [UNESP] (My University, 2014)
This article, an excerpt of the doctorate thesis Trajectories of the urban planning in Araraquara: from the power to decisive centralism to the participative managing plan, intends to dimension the forged urban chain in the State of São Paulo, Brazil. Based on Anhaia Mello' theses - university professor of the College of Architecture and Urbanism of the University of São Paulo (FAU-USP) -, it crystallized in the first elaborated managing plan in the city of Araraquara from 1950 on. This process of French and Anglo-American shades, in Araraquara, changed the knowledge on urban planning, producing an intended effect in the region. During the collection of the primary sources, it was clear that the proposals of FAU-USP incorporated in the urbanization norms of Araraquara, dictating the routes of the development of the urban public politics of the city in the middles of the decade of 1960.
Trajectories of the urban planning: The managing plan of the decade of 1950 and the urban rearranging or reorganization of Araraquara, São Paulo, Brazil
Keywords: Public politics and democracy; Urban development; Urban planning